The Role and Responsibility of Auditors in Reporting Modern Slavery - Zhong, Caichan (2019)
Modern slavery refers to the institutional slavery that exists in current society. Modern slavery can harm people of any age, gender, and race. It widely exists around the world and modern slavery actions happen every day. But, there are also lots of people that work hard to fight against modern slavery. Modern slavery is not only a human rights problem but also a business problem. Eradicating modern slavery is the responsibility of the whole society. This dissertation is attempting to bridge some of the gaps that there is little known on how Auditors can play a role now and future, and their potential to take responsibility in tackling modern slavery. This dissertation aims to analyze this question from two aspects.